The Integration of Rationality and Spirituality: Imam Al-Ghazali's Experience through Ta'lim Rabbani Approach in Acquiring Knowledge - Kholili Hasib; Neneng Uswatun Khasanah (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
This article investigates the integration of rationality and spirituality in the educational philosophy of Imam al-Ghazali, with particular attention to his experience of ta‘līm rabbānī (divine instruction) as a pathway to ma‘rifah (spiritual knowledge). Imam al-Ghazali’s intellectual crisis and subsequent spiritual transformation reflect a shift from reliance on discursive reason to a higher epistemic state grounded in divine guidance. Drawing on al-Munqidh min al-Ḍalāl and key insights from Iḥyā’‘Ulūm al-Dīn, this study analyzes the importance of spirituality or ma'rifah in education. This research employed a literature review grounded in a philosophical approach, wherein analysis was conducted by examining written texts. Methodologies utilized encompass critical review, comparison, summarization, and synthesis, adopting a descriptive-analytical approach to assess various dimensions of the proposed theory. The article argued that al-Ghazali’s ta‘līm rabbānī framework is not a rejection of reason, but a reorientation of reason under the authority of divine truth. The findings suggested that this integrated model provided a relevant paradigm for contemporary Islamic education, particularly in addressing the fragmentation of knowledge and the marginalization of spirituality in academic contexts. In contemporary Islamic education, this model challenges the prevalent separation of intellect and spirituality and calls for a reintegration of ethical, spiritual, and rational dimensions of knowledge in the formation of the human self.